Media, Bureaucracies and Foreign Aid: A Comparative Analysis of the United States, the United Kingdom, Canada, France and Japan - Belle, Douglas A. Van. author. aut Link
192 p.
Keywords: This is the first sustained comparative examination of the importance of media attention on the provision of economic assistance, suggesting that the news media is an important medium for policy makers to gauge potential domestic political pressures and thus the need to be responsive and even anticipatory in addressing problems real or perceived. Particular attention is paid to the responsiveness of bureaucracies, long held to be among the most insulated institutions of government. Cross-national in scope, this book looks at the United States, the United Kingdom, Canada, France and Japan, facilitating a nuanced understanding of the interaction of international and domestic politics as mediated by the media.